IoT-Based Banknotes Saving Automation System - Prasasti, Anggunmeka Luhur; Septiawan, Reza Rendian; Alfarisi, Muhammad Haekal (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
Many problems occur with traditional savings, such as users not knowing the nominal amount that has been saved later, and the authenticity of the money saved. To overcome this problem, the "Savings Storage Automation System with IoT-Based Banknotes" tool was created, this tool aims to help users save money easily and safely. The system design is based on Arduino Mega. The inputs on the Arduino Mega consist of a GY-33 TCS34725 as a color sensor and a keypad to perform functions. The output produced is in the form of nominal data of banknotes that can be seen by the user through an LCD and sent to a database, checking the authenticity of the money is done manually by using ultraviolet. The method used to identify the nominal banknotes is based on the reading of each RGB value and color temperature on each nominal banknote. The average accuracy of reading currency values on real banknotes reaches 88%, while in testing counterfeit banknotes it is 14%. Testing execution time when entering money into savings is 3.57 seconds and data to the database is 6.57 seconds.